2019
DOI: 10.1111/jam.14375
|View full text |Cite
|
Sign up to set email alerts
|

The plant growth‐promoting potential of the mesophilic wood‐rot mushroomPleurotus pulmonarius

Abstract: Aims To demonstrate the plant growth‐promoting potential of a wood‐decay mushroom. Methods and Results A wild strain of a white rot fungus (Pleurotus pulmonarius) was found to convert 10 mmol l−1 L‐tryptophan (TRP) to approximately 15 μg ml−1 indole‐3‐acetic acid (IAA) under the optimal growth conditions of 30°C and pH 5 for 15 days. Results of gas chromatography–mass spectrometry indicated IAA synthesis through the indole‐3‐pyruvic acid pathway when using cellulose as a sole carbon source. The mycelium as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 104 publications
(111 reference statements)
0
2
0
Order By: Relevance
“…The fungi produced maximum auxin on the 18th day (76 µg/ml) (Ünyayar et al 2000), while the same strain Phanerochaete chrysosporium ME446 demonstrated 0.198 µg IAA/ml in broth medium (Ünyayar 2002). Recently, another wood-degrading basidiomycetes Pleurotus pulmonarius was reported to convert 10 mM tryptophan to approximately 15 μg/ml IAA using, cellulose as a sole carbon source (Pham et al 2019). Three white rot fungi Pleurotus ostreatus, Phanerochaete chrysosporium and Trametes versicolor produced IAA when plant biomass (Jatropha seed cake) was used as a substrate.…”
Section: Discussionmentioning
confidence: 99%
“…The fungi produced maximum auxin on the 18th day (76 µg/ml) (Ünyayar et al 2000), while the same strain Phanerochaete chrysosporium ME446 demonstrated 0.198 µg IAA/ml in broth medium (Ünyayar 2002). Recently, another wood-degrading basidiomycetes Pleurotus pulmonarius was reported to convert 10 mM tryptophan to approximately 15 μg/ml IAA using, cellulose as a sole carbon source (Pham et al 2019). Three white rot fungi Pleurotus ostreatus, Phanerochaete chrysosporium and Trametes versicolor produced IAA when plant biomass (Jatropha seed cake) was used as a substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Ligninase production by wood-rotting fungi is also influenced by growth conditions such as temperature and pH. WRF isolates classified as mesophyll fungi can live in a temperature range of 15-40 °C (Pham et al, 2019). The optimum pH for the production of heme peroxidase is at pH of 4.5-5.5 (Acevedo et al, 2011), and for the production of phenol oxidase (laccase) is between pH of 3-7 (Hamid et al, 2013).…”
Section: Introductionmentioning
confidence: 99%